2012
DOI: 10.1038/oby.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin Receptor 4 Deficiency Affects Body Weight Regulation, Grooming Behavior, and Substrate Preference in the Rat

Abstract: Obesity is caused by an imbalance between energy intake and expenditure and has become a major health-care problem in western society. The central melanocortin system plays a crucial role in the regulation of feeding and energy expenditure, and functional loss of melanocortin receptor 4 (MC4R) is the most common genetic cause of human obesity. In this study, we present the first functional Mc4r knockout model in the rat, resulting from an N-ethyl-N-nitrosourea mutagenesis–induced point mutation. In vitro obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(97 citation statements)
references
References 41 publications
9
83
2
3
Order By: Relevance
“…We used MT-II, a drug widely used to assess the effect of MC4-R activation on food intake and body weight (Baird et al, 2011;Blevins et al, 2012;De Jonghe et al, 2012;Mul et al, 2012;Roseberry, 2013). We found its predominant effect at the DMV was to decrease the amplitude of gastric phasic contractions.…”
Section: Discussionmentioning
confidence: 99%
“…We used MT-II, a drug widely used to assess the effect of MC4-R activation on food intake and body weight (Baird et al, 2011;Blevins et al, 2012;De Jonghe et al, 2012;Mul et al, 2012;Roseberry, 2013). We found its predominant effect at the DMV was to decrease the amplitude of gastric phasic contractions.…”
Section: Discussionmentioning
confidence: 99%
“…AVP release is driven by serum osmolality, and inappropriately low plasma levels as seen in central diabetes insipidus lead to a hyperosmolar state with polydipsia and polyuria (38). Interestingly, the Mc4r K314X mutation in the rat described by Mul et al (39) induces polydipsia. In view of the currently reported co-localization of AVP and MC4R, it is tempting to hypothesize that a deficient AVP release in the Mc4r K314X rat may be involved in the pathogenesis of the reported polydipsia.…”
Section: Mc4r and Co-localization With Other Neuropeptidesmentioning
confidence: 99%
“…This is the first study to use the exome sequencing approach to identify exonic variant(s) related to the BMI in an obese Thai (Farooqi et al, 2003;Begriche et al, 2011;Dubern and Clement, 2012;Loos, 2012;Mul et al, 2012;Tsou et al, 2012), did not differ significantly between obese and normal subjects. Subsequently, 65 variants in 60 genes predicted to negatively affect the protein structure and function were chosen for further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a correlation between several genes, such as LEP, LEPR,POMC,PCSK1,FTO,MC3R,MC4R,GNPDA2,TMEM18,QPCTL/GIPR,BDNF,ETV5,MAP2K5/SKOR1,SEC16B,SIM1, TNKS/MSRA, and obesity, using a candidate gene approach or a genome-wide association study (GWAS) (Farooqi et al, 2003;Begriche et al, 2011;Dubern and Clement, 2012;Mul et al, 2012;Tsou et al, 2012). Most of these variants were in the intronic region; therefore, the mechanism leading to the development of disease could not be determined (Dorajoo et al, 2012;Loos, 2012).…”
Section: Introductionmentioning
confidence: 99%